2005
DOI: 10.7326/0003-4819-142-10-200505170-00009
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Accuracy of Rapid Tests for Malaria in Travelers Returning from Endemic Areas

Abstract: Rapid malaria tests may be a useful diagnostic adjunct to microscopy in centers without major expertise in tropical medicine. Initial decisions on treatment initiation and choice of antimalarial drugs can be based on travel history and post-test probabilities after rapid testing. Expert microscopy is still required for species identification and confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
108
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 32 publications
11
108
2
4
Order By: Relevance
“…Studies evaluating other RDTs in non-endemic countries report similar sensitivities as those found for the CareStart™ Malaria HRP-2/pLDH (Pf/pan) Combo Test in the present study: for P. falciparum they ranged from 87.5-99.0%, with one exception of 76.2% [7,10,16-21]. For P. vivax , RDTs detecting pan-pLDH showed sensitivities of 33.5% and 62.0%-95.0%,[7,10,13,18,20,22] compared to 46.0%-93.0% [13] for those RDTs targeting aldolase. The increase of sensitivities at higher parasite densities is a well-known phenomenon with breakpoints around 100/μl ( P. falciparum ) and 500/μl ( P. vivax ) [7,10,13,22,23].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Studies evaluating other RDTs in non-endemic countries report similar sensitivities as those found for the CareStart™ Malaria HRP-2/pLDH (Pf/pan) Combo Test in the present study: for P. falciparum they ranged from 87.5-99.0%, with one exception of 76.2% [7,10,16-21]. For P. vivax , RDTs detecting pan-pLDH showed sensitivities of 33.5% and 62.0%-95.0%,[7,10,13,18,20,22] compared to 46.0%-93.0% [13] for those RDTs targeting aldolase. The increase of sensitivities at higher parasite densities is a well-known phenomenon with breakpoints around 100/μl ( P. falciparum ) and 500/μl ( P. vivax ) [7,10,13,22,23].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies that included P. ovale or P. malariae species reported sensitivities for these species combined between 36 - 95% for pan-pLDH and 7 - 80% for aldolase based RDTs [13]. In addition, a previous study with a study design similar to the present one reported sensitivities for P. ovale and P. malariae of 76.3% and 45.2% respectively [7].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…However, the Immunoquick+4 did not reach the 95% sensitivity for parasite densities >100/µl recommended by the WHO [17]. For P. vivax, MRDTs targeting pan-pLDH show sensitivities from 33.5% and 62.0-95.0% [3,12,15,[18][19][20], compared to 46.0-93.0% [20] [20]. Previously, we demonstrated for a three-band HRP-2/pan-pLDH MRDT in a study design similar to the present one sensitivities for P. ovale and P. malariae of 76.3 and 45.2%, respectively [3].…”
Section: Discussionmentioning
confidence: 99%